2020
DOI: 10.2106/jbjs.rvw.19.00154
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Prolonged Postoperative Narcotic Usage Following Orthopaedic Surgery

Abstract: Background: The purpose of this comprehensive review was to investigate risk factors associated with prolonged opioid use after orthopaedic procedures. A comprehensive review of the opioid literature may help to better guide preoperative management of expectations as well as opioid-prescribing practices. Methods: A systematic review of all studies pertaining to opioid use in relation to orthopaedic procedures was conducted using the MEDLINE, Embase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 72 publications
1
43
0
Order By: Relevance
“…We identified that patients were required to wait longer for their surgery (88-day difference in median wait time from referral to follow-up), and a significantly larger proportion of patients were prescribed opioid-based analgesia (14 percentage points more in the COVID-19 group compared with our historical Controls) preoperatively, despite a lower frequency of opioid use at referral. Given the previously known associations between preoperative opioid use and poorer perioperative surgical outcomes, [9][10][11][12][13][14] urgent attention is required to identify alternative effective non-operative treatment strategies or expedite operative intervention for those awaiting arthroplasty surgery. Increasing use of opioid medication routinely within this healthcare setting may also have larger long-term consequences for public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified that patients were required to wait longer for their surgery (88-day difference in median wait time from referral to follow-up), and a significantly larger proportion of patients were prescribed opioid-based analgesia (14 percentage points more in the COVID-19 group compared with our historical Controls) preoperatively, despite a lower frequency of opioid use at referral. Given the previously known associations between preoperative opioid use and poorer perioperative surgical outcomes, [9][10][11][12][13][14] urgent attention is required to identify alternative effective non-operative treatment strategies or expedite operative intervention for those awaiting arthroplasty surgery. Increasing use of opioid medication routinely within this healthcare setting may also have larger long-term consequences for public health.…”
Section: Discussionmentioning
confidence: 99%
“… 8 More specifically within the arthroplasty population, long-term opioid use preoperatively has been associated with increased risk of perioperative complications, 9 10 poorer functional outcome 11 12 and ongoing opioid dependence postoperatively. 13 14 …”
Section: Introductionmentioning
confidence: 99%
“…Across multiple subspecialties in orthopaedic surgery, the literature has consistently demonstrated that preoperative opioid use strongly predicts prolonged opioid demand after surgery. 7,[10][11][12][13][14][15][16][17][18][19][20][21]25,26 Anthony et al 19 conducted a multicenter review of 4,946 ACL reconstructions and found that patients with preoperative prescriptions were 4.06 times (95% CI, relative risk 3.33-4.96) more likely to be refilling prescriptions at 2 months and 5.35 to 7.67 times more likely at all time points between 3 and 12 months after surgery. The majority of patients discontinued opioid use after the first postoperative month, with 10% or less refilling at 2 months and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Previous substance use was among the top predictors for adverse opioid-related outcomes, which included previous benzodiazepines, muscle relaxants, opioids, alcohol, cannabis, and cocaine use. Lavoie-Gagne and colleagues 25 performed a systematic review of 45 studies including 458,993 patients across various orthopaedic subspecialties to identify risk factors for prolonged opioid use after surgery. Across all studies, previous substance abuse aside from tobacco and alcohol, use of other medications, psychiatric comorbidities, BMI greater than 40, chronic pain conditions, fibromyalgia, and migraines were all associated with prolonged opioid use after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation